Mechanisms of Kaempferol in the treatment of diabetes: A comprehensive and latest review - Yang, Yan; Chen, Zhengtao; Zhao, Xiaoyan; Xie, Hongyan; Du, Lian; Gao, Hong; Xie, Chunguang (Frontiers in Endocrinology, 2022)
Obesity–insulin resistance–β-cells apoptosis” is an important trilogy of the pathogenesis of type 2 diabetes. With the global pandemic of obesity and diabetes, continuous research and development of new drugs focuses on the prevention of the pathological progress of these diseases. According to a recent study, the natural product kaempferol has excellent antidiabetic effects. Therefore, this review comprehensively summarized the frontier studies and pharmacological mechanisms of kaempferol in the treatment of diabetes. The successful research and development of kaempferol may yield a significant leap in the treatment of diabetes and its complications.